Anticipating the Future of Green Human Resource Management in Riyadh’s Governmental Middle Schools Using the Delphi Method - Altowairqi, Fatmah Hameed (Journal of Educational and Psychological Sciences, 2023)
The primary aim of this study was to identify a forward-looking approach towards green human resources management, using the Delphi method. The Delphi method is a well-established research method used in various fields to gather expert opinions and get consensus on a particular topic. A questionnaire was prepared, and the study was conducted during the third semester of the year 1444 hijri. A sample of 12 experts, comprising Ph.D. and Master’s degree holders in education management, was selected to participate in this study. The study was divided into two themes, addressing individual and organizational levels of green human resource management. The results of the analysis revealed that a forward-looking approach towards green human resources management is possible, and a proposal for such an approach was developed in accordance with the Delphi method. The proposal outlined the main pillars of the vision, premises, and steps required to implement green human resources management in public middle schools. This included a focus on green strategy, green human resources, and green productivity. Another notable recommendation of this study was to conduct courses for enhancing future studies in education research. This would create awareness among educators and policymakers regarding the benefits of adopting green human resources management, leading to long-term sustainability in public middle schools. Furthermore, include such a research related as a priority in the research centers of the Ministry of Education.